2016
DOI: 10.1103/physrevb.94.045202
|View full text |Cite
|
Sign up to set email alerts
|

Effects of molecular dipole orientation on the exciton binding energy ofCH3NH3PbI3

Abstract: We present a simple interacting tight-binding model for excitons, which is used to investigate the dependence of the exciton binding energy of CH 3 NH 3 PbI 3 over the disorder induced by the molecular motion at room temperature. The model is fitted to the electronic structure of CH 3 NH 3 PbI 3 by using data from density-functional theory and Born-Oppenheimer ab initio molecular dynamics, and it is solved in the mean-field approximation. When a finite-scale analysis is performed to extract the energetic of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…In a theoretical study, Motta et al found that the exciton binding energy can vary depending on the degree of disorder in the material, concluding that the excitonic properties of MAPbI 3 largely depend on the electronic structure of the PbI 3 inorganic lattice. [19] This was also observed in an experimental study by D'Innocenzo et al, who showed that the degree of the exciton absorption peak varies significantly, depending on the microstructure of the sample, where small grains suggest lower exciton binding energies. [10] In a consecutive work, Grancini et al have proven that the correlation between microstructure and binding energy is due to the fact that the effective dielectric constant is sensitive to temporal alignment of the MA cations.…”
Section: Absorptionsupporting
confidence: 62%
See 1 more Smart Citation
“…In a theoretical study, Motta et al found that the exciton binding energy can vary depending on the degree of disorder in the material, concluding that the excitonic properties of MAPbI 3 largely depend on the electronic structure of the PbI 3 inorganic lattice. [19] This was also observed in an experimental study by D'Innocenzo et al, who showed that the degree of the exciton absorption peak varies significantly, depending on the microstructure of the sample, where small grains suggest lower exciton binding energies. [10] In a consecutive work, Grancini et al have proven that the correlation between microstructure and binding energy is due to the fact that the effective dielectric constant is sensitive to temporal alignment of the MA cations.…”
Section: Absorptionsupporting
confidence: 62%
“…It has been shown that the exciton binding energy of MAPbI 3 depends on various parameters, in particular, it is sensitive to the microstructure of the perovskite layer. In a theoretical study, Motta et al found that the exciton binding energy can vary depending on the degree of disorder in the material, concluding that the excitonic properties of MAPbI 3 largely depend on the electronic structure of the PbI 3 inorganic lattice . This was also observed in an experimental study by D'Innocenzo et al, who showed that the degree of the exciton absorption peak varies significantly, depending on the microstructure of the sample, where small grains suggest lower exciton binding energies .…”
Section: Investigating Electronic Properties With Temperature Dependementioning
confidence: 74%
“…This is further supported by a recent theoretical study by Motta et al in which the impact of the degree of molecular dipole orientational disorder -which could be induced by the grain size variation -on the binding energy in the high temperature phase of MAPbI 3 was found to be only B10%. 44 To generalise our findings for MAPbI 3 to other perovskite compositions, we repeated the measurements on a state-of-theart triple-cation lead mixed-halide perovskite, Cs 0.05 (MA 0.17 -FA 0.83 ) 0.95 Pb(I 0.83 Br 0.17 ) 3 . 2 We consider two significantly different morphologies of this perovskite composition, namely a planar polycrystalline thin film and a film with the perovskite infiltrated into a thick mp-Al 2 O 3 scaffold (corresponding SEM images are shown in Fig.…”
Section: View Article Onlinementioning
confidence: 98%
“…Finally, in Figure 10(d,e,f) a random field to mimic a certain degree of thermally-induced disorder has been introduced. As previously proposed for perovskites, 59 this was achieved by adding a small random fluctuation, uniformly distributed in an interval [0, ε], to the onsite energy of every unit of the stacked model. Introduction of this fluctuation slightly increases the match between blue and red profiles in Figure 10(e) and 10(f) in comparison to Figure 10(b) and 10(c).…”
Section: Modeling the Electron-phonon Coupling By Monitoring The Vibr...mentioning
confidence: 99%